Night-to-night variability of polygraphy in children with sleep disordered breathing symptoms - AY, NADİYE PINAR (My University, 2023)
Introduction: Polygraphy (PG) can be used as an alternative test for the diagnosis of obstructive sleep apnea syndrome (OSAS) in children. Night‐to‐night variability of PG in children is not known. Our aim was to determine whether a single night PG was reliable for OSAS diagnosis in children with symptoms of sleep‐disordered breathing (SDB). Materials and Methods: Otherwise healthy children who had been evaluated for symptoms of SDB were included. Two nocturnal PGs were performed 2–7 days apart. Demographic and clinical characteristics, Pediatric Sleep Questionnaire, and modified Epworth Sleepiness Scale were recorded. OSAS was diagnosed if obstructive apnea–hypopnea index was (oAHI) ⩾ 1/h and classified as mild (oAHI: 1–4.9/h), moderate (oAHI: 5–9.9/h), and severe (oAHI ⩾ 10/h). Results: Forty‐eight patients were included (37.5% female, age 10.8 ± 3.9 years) to the study. There were no significant differences in oAHI values and other respiratory parameters between the two PGs (p > 0.05). Thirty‐nine children were diagnosed with OSAS if the highest oAHI over any single night was used for diagnosis. Thirty‐ three of the 39 children (84.6%) were diagnosed with OSAS with the first PG while 35 of 39 (89.7%) children were diagnosed with OSAS with the second PG. There was an agreement for identifying OSAS and its severity between the two PGs in our study even though there were few individual intra‐subject differences in oAHI. Conclusion: There was no significant first‐night effect for PG in this study which suggests that a single night PG is adequate for diagnosis of OSAS in children with SDB‐ related symptoms.
Keywords: obstructive sleep apnea; polygraphy; variability